Comparison of Perceived Stigmatization, Social Avoidance and Self- Cconcept among male and female Vitiligo Patients - Naz, Komal; Nawaz, Nazia (The Lighthouse Journal of Social Sciences, 2024)
Vitiligo is a non-infectious skin disease characterized by white skin patches that are distinctive in size and shape caused by the loss of pigment cells in the skin. The disease is equally prevalent in both genders regardless of age, race, and ethnic groups. The disease does not cause any disability and pain on the part of the individual but gives rise to many psychological concerns like depression, anxiety, social avoidance, perceived stigmatization, low self-concept, and low self-esteem. The objective of the study was to assess the impact of perceived stigmatization and social avoidance on vitiligo patients and to analyze the stigmatization effect on self-concept. The effect of exposed and un-exposed patches of skin on self-concept was also an area of concern. A sample of N=100 (n=50 male and n=50 female) between ages 15 to 50 years suffering from vitiligo were selected from dermatology departments of different hospitals and the general population by using a purposive sampling technique. Perceived stigmatization scale, Social avoidance and distress scale, and Robson self-concept scales were administered to the selected sample. The results indicated that there exist no significant difference in perceived stigmatization and social avoidance among male and female vitiligo patients. The predictor stigmatization .091 is insignificant and has no significant effect on self-concept r 2=1.44. Also, there is no significant difference between the self-concept of individuals with vitiligo on exposed (M= 22.44 and SD = 6.25) and un-exposed body parts (M= 24.44 and SD= 5.29). It is concluded from the current study that both genders are the victim of stigmatization and social avoidance due to their disfigured appearance and the condition leaves a devastating impact on self-concept no matter whether the person has patches on exposed or un-exposed parts of the body.